Analyse des stratégies d’apprentissage dans une méthode d’apprentissage par problèmes : le cas d’étudiantes en soins infirmiers - Caroline Larue; Mohamed Hrimech (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Several higher education institutions have adopted problem-based learning as an educational method. But, as far as we know, very few studies try to describe the strategies which are used by students in order to succeed in a problem-based learning context. The purpose of this research is to study those strategies. The analysis of the verbatim obtained from 31 nursing students uncovered the main strategies and their respective frequency. The results suggest that the students are more likely to use strategies based on surface treatment of the information than in-depth learning strategies. This preference is maintained even though they were told that in-depth learning strategies increase their academic achievements.